Teacher’s Barriers in Using Flashcards as Interactive Media in Teaching English Vocabulary - Sri Lestari; Lilies Youlia Friatin; Etika Rachmawati (Journal of English Education Program (JEEP), 2026)
Vocabulary plays a fundamental role in English language acquisition as it supports the development of language skills. Vocabulary mastery can be developed by optimizing the use of interactive media such as flashcards which offer an effective and engaging activity in teaching vocabulary, especially for young learners. This study was carried out to explore the barriers faced by an English teacher in using interactive flashcards in an elementary school in Ciamis and how the teacher overcomes the barriers found. This study used a qualitative case study and was taken through classroom observation and semi-structured interviews as research instruments. Thematic analysis was used to analyse the data from the classroom observation and interviews. The research participants involved in this study were a second grade English teacher. The findings revealed three main challenges: (1) students' limited reading and writing skills; (2) difficulty in time management due to varying student response times and lack of time management features in the flashcard application; and (3) different levels of vocabulary mastery among students, which affected the overall effectiveness of teaching. To overcome these challenges, the teacher implemented various adaptive strategies such as verbal repetition, adjusted time allocation, and differentiated teaching based on the needs of each student. This study highlights the importance of teacher adaptability to ensure the effective use of interactive media in teaching vocabulary.